UNMASKING THE ANTAGONIST: A PSYCHOLOGICAL ANALYSIS OF PSYCHOPATHY IN JAMES PATTERSON’S FEAR NO EVIL - Barus, Efendi; Wardana, Fitra Andira; Purwarno, Purwarno (JOURNAL OF LANGUAGE, 2025)
This study explores the psychological dimensions of antagonism in James Patterson’s novel Fear No Evil, focusing on the construction of the antagonist Matthew Butler as a psychopath. Employing a qualitative descriptive approach and drawing upon Robert Hare’s Psychopathy Checklist-Revised (PCL-R), the analysis identifies how Butler exhibits core psychopathic traits such as lack of empathy, manipulativeness, impulsivity, and emotional shallowness. Data were collected through close reading and textual analysis, emphasizing the antagonist’s actions, dialogue, and interactions with other characters. The findings reveal that Butler’s characterization is deeply rooted in psychopathic tendencies that serve not only as a narrative device but also as a reflection of broader psychological realities in crime fiction. By integrating psychological theory with literary analysis, this research contributes to the field of literary psychology, offering insights into how contemporary thrillers represent mental disorders and how antagonistic characters function to intensify narrative conflict. The study further underscores the significance of interdisciplinary approaches in understanding the intersection of literature, psychology, and criminology, particularly in examining how fictional psychopaths are constructed in popular culture.